Dual Synthesis of Silver and Iron Oxide Nanoparticles from Edible Green Amaranthus Viridis and their In vitro Antioxidant Activity and Antimicrobial Studies - Kotakadi, Venkata S.; Kolapalli, Bhulakshmi; Gaddam, Susmila Aparna; Ramana, Sai Gopal Divi Venkata (Current Biotechnology, 2021)
Background: There is an increasing commercial demand for nanoparticles due to their wide applicability in various areas, such as chemistry, catalysis, energy and medicine. Metallic nanoparticles are traditionally synthesized by wet chemical techniques where the chemicals used are quite often toxic and flammable. Objective: In the present study, we have described a simple, cost-effective and environmentally- friendly technique for green synthesis of silver and iron nanoparticles by using the aqueous extract of leafy vegetable Amaranthus viridis as a reducing agent. Methods: The silver and iron nanoparticles (Av-AgNPs, Av-IONPs) were characterized by different spectral methods. The surface plasmon resonance spectrums of Av-AgNPs, Av-IONPs were recorded at 422nm and 261nm. The scanning electron microscopy (SEM) analysis reveals that the Av-AgNPs and Av-IONPs are roughly spherical in shape. Energy dispersive absorption spectroscopy (EDAX) of biosynthesized Av-AgNPs and Av-IONPs indicates the reduction of silver ions to elemental silver and iron ions to elemental iron. Results: The particle size analysis of Av-AgNPs and Av-IONPs was carried out by the dynamic light scattering (DLS) method; the results reveal both Av-AgNPs and Av-IONPs to be polydispersed in nature. The average particle size of Av-AgNPs is 55.8 nm with a polydispersed index (PI) of 0.297; similarly, the average particle size of Av-IONPs is 80.6 nm with a polydispersed index (PI) of 0.469. Zeta-potential of Av-AgNPs was detected at -24.6 mV and Av-IONPs were detected at 28.8 mV; the result reveals that their high stability may be due their high negative charge and positive charge, respectively. The dual synthesized Av-AgNPs and Av-IONPs exhibited excellent antioxidant activity by DPPH, H2O2 and NO methods. DPPH was proven to be the best when compared with the other two methods. The biosynthesized Av-AgNPs and Av-IONPs proved to have very good antimicrobial activity against gram +ve and gram –ve bacteria. Conclusion: Compared with the standard antibiotic, there are several reports on the green synthesis of metal nanoparticles using various plant parts, but here, edible leafy vegetable Amaranthus viridis was used for biosynthesis of both Av-AgNPs and Av-IONPs.
Keywords: silver nanoparticles